New report of Coproica vagans (Diptera: Sphaeroceridae) from Iran - Emad Changizi; Mohammad Mehdi Darvishi (نامه انجمن حشره‌شناسی ایران, 2019)
During May 2019, a study in Shirvān city (North Khorasan province) to investigate the infestation of livestock farms with various insect species was carried out. In this study, large quantities of flies belonging to the Sphaeroceridae family were collected using light traps. The genus and species of these flies were identified as Coproica vagans (Haliday, 1833). This species is a new record for the Iranian insect fauna.